2018
DOI: 10.1002/ccd.27715
|View full text |Cite
|
Sign up to set email alerts
|

Three‐year clinical outcomes of patients treated with everolimus‐eluting bioresorbable vascular scaffolds: Final results of the ABSORB EXTEND trial

Abstract: Background There is still limited data on the very long term clinical outcomes after ABSORB BRS in daily practice. We sought to evaluate the 3 year‐performance of the Absorb bioresorbable vascular scaffolds for the treatment of low/moderate complexity patients enrolled in the ABSORB EXTEND trial. Methods ABSORB EXTEND is a prospective, single‐arm, open‐label clinical study in which 812 patients were enrolled at 56 sites. This study allowed the treatment of lesions ≤28 mm in length and reference vessel diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…A total of 1,157 studies were screened for inclusion in our meta‐analysis, as shown in the flow‐chart for the selection process in Figure . Three studies were excluded since not designed as randomized clinical trials, one since not providing clinical outcome data, one study since not providing data on individual components of the primary composite endpoint, whereas one study was excluded since enrolling patients treated for PAD …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 1,157 studies were screened for inclusion in our meta‐analysis, as shown in the flow‐chart for the selection process in Figure . Three studies were excluded since not designed as randomized clinical trials, one since not providing clinical outcome data, one study since not providing data on individual components of the primary composite endpoint, whereas one study was excluded since enrolling patients treated for PAD …”
Section: Resultsmentioning
confidence: 99%
“…Three studies were excluded since not designed as randomized clinical trials, 18,20,21 one since not providing clinical outcome data, 22 one study 19 since not providing data on individual components of the primary composite endpoint, whereas one study was excluded since enrolling patients treated for PAD. 23 After the exclusion of studies with duplicate data ad meta-analysis, 11 randomized clinical trials (RCTs) [14][15][16][24][25][26][27][28][29][30][31] were finally included in our analysis, with an overall population of 10,707 patients.…”
Section: Eligible Studiesmentioning
confidence: 99%
“…Furthermore, the angiographic surveillance at 5 years showed satisfactory results with an overall late luminal loss of 0.26 ± 0.42 mm 11 . Furthermore, a large‐scale study of 812 patients with predominately stable coronary artery disease and non‐complex lesions reports 3‐year rates for MACE, TLR, and ScT of 9.2%, 3.1%, and 2.2%, respectively 12 . Besides, randomized‐controlled trials with long‐term follow‐up comparing BRS and DES are available.…”
Section: Discussionmentioning
confidence: 92%
“…In particular another retrospective study showed favourable outcomes with EE-BRS at 2 years, comparable to modern DES in DM patients [29]. Similarly, other studies, have shown favourable results with EE-BRS at longer follow-up, however these studies were not exclusively focussed on DM patients [30, 31]. However, our data reveals similar clinical outcomes as the everolimus-eluting stent (EES) arm from a pooled database from the SPIRIT and COMPARE trials in DM patients [11].…”
Section: Discussionmentioning
confidence: 99%